Isolation and Identification of Dominant Bacteria from Raw Donkey Milk Produced in a Region of Morocco by QIIME 2 and Evaluation of Their Antibacterial Activity - Reda Derdak; Javier Quinteiro; Souraya Sakoui; Boutaina Addoum; Jorge Rodríguez Castro; Manuel Rey Méndez; Abdelaziz Soukri; Bouchra El Khalfi (The Scientific World Journal)
Recently, the interest in donkey milk has increased considerably because it proved high nutritive and functional values of their ingredients. Its chemical composition is widely studied, but its microbiota, especially lactic acid bacteria, remains less studied. This study focuses on analyzing, isolating, and identifying lactic acid bacteria and evaluating their capacity to produce biomolecules with antibacterial activity. Among 44 strains identified, 43 are Gram-positive, and most are catalase-negative and cocci-shaped. Five strains were selected to evaluate their antibacterial activity against Listeria monocytogenes, Staphylococcus aureus, and Escherichia coli. Different induction methods allowed to amplify the antibacterial effects against these pathogenic strains.